2010
DOI: 10.1007/s11071-010-9864-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatial behavior of an epidemic model with migration

Abstract: It was reported that there are traveling patterns in the spatiotemporal data of epidemics (Cummings et al., Nature 427:344, 2004; Grenfell et al., Nature 414:716, 2001). To well understand the mechanism, we present a spatial epidemic model with migration, which means that the individuals exhibit a correlated motion toward certain direction, and obtain traveling pattern. Our results may be helpful to understand the mechanism of the spatiotemporal epidemics and have potential application of control of the epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…In addition, in this work, we only consider the general preventive behavioral response of crowd. However, the dynamics of an epidemic may be very different due to the behavioral responses of people, such as adaptive process [44] , migration [61] , vaccination [39] , and immunity [62] . This work just provides a starting point to understand the coupling effect between the two spreading processes, a more comprehensive and in-depth study of personalized preventive behavioral responses shall need further effort s to discover.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In addition, in this work, we only consider the general preventive behavioral response of crowd. However, the dynamics of an epidemic may be very different due to the behavioral responses of people, such as adaptive process [44] , migration [61] , vaccination [39] , and immunity [62] . This work just provides a starting point to understand the coupling effect between the two spreading processes, a more comprehensive and in-depth study of personalized preventive behavioral responses shall need further effort s to discover.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…R 0 is called the basic reproduction ratio of system (3), which describes the average number of newly infected cells generated from one infected cell at the beginning of the infectious process. This quantity determines the thresholds for disease transmissions.…”
Section: Existence Of Traveling Wavesmentioning
confidence: 99%
“…In [1], by constructing a pair of upper-lower solutions, the existence of a traveling wave solution connecting the disease-free steady state and the endemic steady state was given. In recent years, there has been a fair amount of work on epidemiological models with spatial diffusion (see, e.g., [2][3][4][5][6]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Driessche and Arino [18] established an epidemic patch model for n cities and analyzed the impact of population mobility on spatial distribution. Cui et al [19] proposed a spatial infectious disease model with migration which has the potential value for disease control. Li [20] showed that pattern transition from stationary pattern to patch invasion appears to be possible in a fully deterministic parasite-host model.…”
Section: Introductionmentioning
confidence: 99%